Musical Habits and Smartphone Addiction of College Students: Mediating Role of Self-Control - Weihong; Gendron, Michael; Lee-Partridge, Joo Eng (The Institute of Academic Research and Publication (IARP), 2024)
This study uses theories of habit and self-control to explore the relationship between musical habits and smartphone addiction among college students. Our findings reveal that self-control mediates this relationship, with individual differences playing a significant role. While musical listening habits, impacted by personal genre preferences, positively impact self-control, active music engagement, through playing an instrument and/or creating music, negatively affects it. We suggest using interventions to promote mindful music engagement to mitigate smartphone addiction. These insights contribute to understanding how music habits influence digital behaviors and offer practical strategies for fostering healthier smartphone use among college populations.